Penegakan Hukum Melalui Restorative Justice dalam Penyelesaian Tindak Pidana Penganiayaan di Wilayah Hukum Polres Bantul - Makhfudzin Rosyid; Harti Winarni (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study examines law enforcement through a restorative justice approach in resolving criminal acts of assault within the jurisdiction of the Bantul Police. This approach offers an alternative way to resolve criminal cases, emphasizing restorative justice, aimed at restoring relationships between perpetrators, victims, and the community. The main objective of this study is to analyze how investigators implement restorative justice and to identify obstacles encountered in its implementation in the field. The methods used in this study are normative and empirical juridical. The normative juridical approach is conducted by examining laws and regulations governing restorative justice, while the empirical approach is conducted through a case study of the implementation of assault case resolution at the Bantul Police. Data were obtained from documentation, interviews with investigators, and related parties in the mediation process. The results of the study indicate that the resolution of criminal acts of assault through restorative justice is implemented in the form of mediation between the perpetrator and victim, facilitated by investigators. This process prioritizes deliberation and consensus to achieve peace and avoids formal legal proceedings. However, its implementation has not run smoothly. Some of the main obstacles identified include low public legal awareness, victims' unpreparedness for reconciliation, and limited police understanding and skills in implementing restorative justice principles. Therefore, strategic efforts are needed, such as strengthening regulations supporting restorative justice, training for law enforcement officers, and ongoing community outreach to ensure this approach can be optimally implemented in resolving assault cases.